THEORETICAL ASPECTS OF COUNTERING TERRORISM AND EXTREMISM IN CENTRAL ASIA (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the theoretical foundations of countering terrorism and extremism in the Central Asian region, highlighting that these phenomena acquire particular significance due to the region’s geopolitical position, ethno-confessional diversity, and the transboundary nature of threats. The aim of the study is to identify the main methodological approaches that allow for the development of effective models to address these challenges. As a research basis, normative, manipulative, structural-functional, and comparative methods were employed, enabling terrorism and extremism to be analyzed both as a multidimensional socio-political phenomenon and as an interdisciplinary system of knowledge. During the analysis, the key characteristics of these phenomena were clarified, their general and specific manifestations in the context of Central Asia were identified, and models of cooperation among regional states in the field of security were outlined. The practical significance of the study lies in the possibility of applying its results in the development of national security strategies and concepts, improving the normative-legal framework, and in other related areas.
Keywords: national security, terrorism, extremism, counteraction, national interests.